Silhouette Study Through Management Plans in World Heritage Sites - Nuray ÖZKARACA ÖZALP; Hicran Hanım HALAÇ (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2024)
The protection and sustainability of heritage sites in today's cities is an important issue in our country as well as all over the world, and it is a big problem to protect and manage these areas to the future. In this direction, site management plans prepared for heritage sites are of great importance. High or incorrect construction has become one of the most important problems of many world heritage sites and threatens the original silhouettes, vantage points and urban panoramas of cities, causing these values to lose their meaning and importance over time. For this reason, many cities, areas or structures of important cultural heritage are removed from the UNESCO World Heritage List or included in the List of World Heritage in Danger. The issue of preserving the silhouette is an important issue that needs to be addressed in Turkey, where the assets worth protecting are unique in number and value. In this study; In order to determine whether studies have been carried out to preserve the original features such as general appearance, silhouette, and scenic points that contribute to the Outstanding Universal Value of heritage sites, content has been scanned with the keywords "silhouette", "landscape" and "view".